Implementation of Multimodal Text in Critical Reading Learning at Superior High School in Sukabumi Regency - Rima Nurkomala; Setyawan Pujiono (Journal of Educational Sciences, 2026)
Critical reading using monomodal texts often leads to suboptimal learning outcomes; therefore, the implementation of multimodal texts is needed in the learning process. This study aims to describe the implementation of multimodal texts in critical reading learning at superior high schools in Sukabumi Regency. This study employed a descriptive qualitative method conducted at three superior high schools in Sukabumi Regency: Albayan Superior Islamic Boarding Senior High School, Adzkia Islamic Integrated Senior High School, and Alkausar Insan Cendekia Senior High School. Data were collected through classroom observations, reviews of six lesson plan documents, and interviews with teachers and students. The data were reduced, presented, analyzed, and interpreted using triangulation techniques. The results showed that multimodal texts had been implemented effectively in critical reading learning. The average score of lesson plan reviews was 93.48%, while learning observations reached 90.74%. The implementation integrated linguistic, visual, audiovisual, gestural, and spatial modes, which effectively improved students’ understanding, participation, critical thinking, and creativity in learning activities.